2018
DOI: 10.1039/c8ra01176a
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent time-set technique controlling the temperature of magnetic-hyperthermia-ablation for tumor therapy

Abstract: Magnetic-hyperthermia-ablation is considered as an effective and minimally invasive technology for tumor therapy. However, inappropriate temperature control could induce an excessively high temperature which brings potential safety problems and limits clinical transformation of this technique. Herein, aiming to control the temperature during magnetic hyperthermia ablation, we develop an intermittent time-set technique for temperature control in magnetic hyperthermia ablation of tumors using a polylactic-coglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Most MFH laboratories use much lower amplitudes, of order 10-15 kA/ m [42], for which the eddy currents, especially in small animal models, are negligible. This may explain why pulse MFH has been seldom used to date, with the exception of a few reports on its use, to obtain high thermal doses and cell death in vitro [43]; to maintain constant temperatures in a murine treatment model [44]; and as part of a pulsatile drug release strategy [45,46]. No previous studies have focused on dose-localization and biological outcomes per se, as in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Most MFH laboratories use much lower amplitudes, of order 10-15 kA/ m [42], for which the eddy currents, especially in small animal models, are negligible. This may explain why pulse MFH has been seldom used to date, with the exception of a few reports on its use, to obtain high thermal doses and cell death in vitro [43]; to maintain constant temperatures in a murine treatment model [44]; and as part of a pulsatile drug release strategy [45,46]. No previous studies have focused on dose-localization and biological outcomes per se, as in this work.…”
Section: Discussionmentioning
confidence: 99%
“…This means that these NPs show significant heating capability at the lowest field frequency studied. C), and that the body temperature is around 37 • C, these NPs were capable of achieving the mild hyperthermia-required temperature and acting as hyperthermia agents, which could be controlled through an intermittent time-set technique [33].…”
Section: Magnetic Hyperthermia (Mh) Measurementsmentioning
confidence: 99%
“…At this amplitude and frequencies of 270.6 kHz and 161.6 kHz, MnFe2O4 NPs reached a temperature variation of ~5 °C in 120 s, while the presence of 20% calcium led to a better heating performance of the ferrite, achieving a variation of ~6 °C and ~7 °C at 270.6 kHz and 161.6 kHz, respectively. Considering that the viability of cancer cells can be affected by mild hyperthermia (~42 °C), and that the body temperature is around 37 °C, these NPs were capable of achieving the mild hyperthermia-required temperature and acting as hyperthermia agents, which could be controlled through an intermittent time-set technique [33].…”
Section: Cytotoxicity Of Citrate-functionalized Ca-mn Ferrites On The...mentioning
confidence: 99%
“…For example, Engelmann et al [107] demonstrated that tissue damage depends not only on the bulk temperature and duration of treatment, but also on the cell type and thermal energy deposited per cell during treatment. Concerning the inconvenient thermal control through the dosage of nanoparticles, as large dosage can induce excessive temperature and low dosage might not be enough to kill cancer cells, Tang et al [108] have recently demonstrated that a simple intermittent time-set technique could be used to control and maintain the enhanced temperature during the magnetic hyperthermia in cancer therapy.…”
Section: Implications Of Magnetic Dipole-dipole Interactions In Magnetic Hyperthermiamentioning
confidence: 99%